Al-Ahadith al-Mushtahirah ‘ala Alsinah Mujtama’ Atsyih al-Muta’alliqah bi as-Shalah: Dirasah Naqdiyyah - Ariani, Safrina; Abullais, Mohammed (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
This research aims to collect the popular hadiths related to the prayer in the society of Aceh, Indonesia, and to evaluate their chain of transmission and text. In its preparation, two approaches were used: the inductive approach to collect these hadiths and information related to them from books and basic references on the subject, both classic and modern, and the critical approach to evaluate these hadiths. The research collected seven popular hadiths about the prayer in the community of Aceh, Indonesia. After verification and evaluation, it was concluded that three of them are sahih hadith. One of them is weak, and three of them are very weak or fabricated hadith.